Peptides for Health Benefits 2019 Volume 2 - Hernández-Ledesma, Blanca; Martínez-Villaluenga, Cristina (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In recent years, peptides have received increased interest from the pharmaceutical industry. The high potency, specificity, and safety profile are the main strengths of bioactive peptides as new and promising therapies that may fill the gap between small molecules and protein drugs. These positive attributes have renewed interest in the discovery, optimization, and development of peptides as pharmacological therapy. Among bioactive peptides, those released from food sources have acquired importance as nutraceutical and active components in functional foods because they possess regulatory functions that can lead to health benefits. This Special Issue covers a selection of recent research papers and reviews in the field of bioactive peptides. It covers all aspects of peptide research in relation to health promotion. In particular, it emphasizes current knowledge and research trends concerning bioactive peptides, including identification and quantification of peptides from new sources, methods for their production and purification, structure-function relationships, mechanisms of action, in vitro and in vivo assays for the evaluation of their bioactivity, physiological evidence to support health benefits, and peptide stability and bioavailability. Papers regarding the development of new drugs, functional foods, or nutraceuticals based on bioactive peptides were also considered.